Expanding Bipolar X-Ray Structure after the 2006 Eruption of RS Oph - Montez, R. (2022)
We report on the detection and analysis of extended X-ray emission by the Chandra X-ray Observatory stemming from the 2006 eruption of the recurrent nova RS Oph. The extended emission was detected 1254 and 1927 days after the start of the 2006 eruption and is consistent with a bipolar flow oriented in the East-West direction of the sky with opening angles of approximately 70°. The length of both lobes appeared to expand from 1.″3 in 2009 to 2.″0 in 2011, suggesting a projected expansion rate of 1.1 ± 0.1 mas day-1 and an expansion velocity of 4600 km s-1 (D/2.4 kpc) in the plane of the sky. This expansion rate is consistent with previous estimates from optical and radio observations of material in a similar orientation. The X-ray emission does not show any evidence of cooling between 2009 and 2011, consistent with free expansion of the material. This discovery suggests that some mechanism collimates ejecta away from the equatorial plane, and that after that material passes through the red giant wind, it expands freely into the cavity left by the 1985 eruption. We expect similar structures to arise from the latest eruption and to expand into the cavity shaped by the 2006 eruption.